Changing portrayal of women during the late modern period in regards to visual communication design. Issue 4 (8th August 2022) - Acan, Vildan; Aygenc, Erdal
Abstract : The Industrial Revolution, world wars, the post-war periods, herewith called the Late Modern period, along with technological advances created a series of social changes in the world. As this transformation became more visible in social life, it has also manifested itself in visual forms such as painting, photography or posters. These social changes, influencing women's lives directly, had also an impact on the manner they were addressed in visual forms. In this regard, this study is centred on the history of visual communication design with a visual cultural approach to observe a connection between the changes that occurred in social life during each period and their effects on the portrayal of women while at the same time it also examines these representations in relation to the development of poster design. Five images produced as advertising and posters ranging from the Industrial Revolution to the Second-Wave Feminism era were selected randomly and examined as illustrative case studies. Zeitgeist approach was used reviewing the periods and countries where these posters were produced. This small study exhibits how the style of women's representation can transform depending on the changing conditions of the era.